Contemporary Mindfulness and Transreligious Learning Paths of Mental Health Professionals - Husgafvel, Ville (Religions, 2023)
In this article, we apply and assess the concept of transreligiosity in the study of formally educated and licensed psychologists and psychotherapists in Finland who integrate mindfulness practices in their professional toolkit. Our analytical focus complements the discussion on the use of religious and spiritual traditions as therapeutic resources by turning scholarly attention from individual coping tools to the professional skills of therapeutic work and from complementary and alternative medicine (CAM) practices to mainstream health care and education. In the field of mindfulness research, we add to the cumulative body of ethnographic approaches by analyzing the mindfulness-related individual learning paths of mental health professionals through qualitative interview data. Based on our analysis, we conclude that the professional skills of using mindfulness practices in secular health care and education can result from transreligious learning trajectories, in which psychologists and psychotherapists supplement science-based academic education with learning in Buddhist communities and training with Buddhist teachers. This role of Buddhist environments and resources points to a blind spot in the current understanding of adult and professional learning, in which the value and position of religious traditions as possible complementary sources of professional knowledge and skills are not sufficiently recognized.